Trends in CTGF Expression in Renal and Chorioretinal Tissues Following Metformin and SGLT2 Inhibitor Treatment in Diabetic Rats - Maimun Syukri; Lia Meuthia Zaini; Arief Sjamsulaksan Kartasasmita; Tjahjono Darminto Gondhowiardjo; Ronny Lesmana; Putri Nabillah Mulya (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Connective tissue growth factor (CTGF) plays a central role in fibrotic processes affecting both renal and retinal tissues in diabetes. Although sodium-glucose cotransporter 2 (SGLT2) inhibitors have been shown to exert renoprotective and antifibrotic effects, their impact on CTGF expression in renal and retinal tissues has not been clearly established. This preliminary study was conducted to evaluate whether SGLT2 inhibitors (SGLT2i) could influence CTGF expression in the kidneys and eyes of diabetes-induced rats.METHODS: After two weeks of adaptation, 24 rats were randomized and distributed equally into four groups (n=6 each): 1) Healthy Control, healthy rats without diabetic induction; 2) Negative Control, diabetic rats induced with streptozotocin (STZ) without treatment; 3) Metformin Group, diabetic rats treated with metformin; and 4) SGLT2i Group, diabetic rats treated with empagliflozin. Following eight weeks of intervention, CTGF expression was analyzed by Western blot in renal tissue (right kidney) and chorioretinal tissue (right eye). Four samples per group yielded analyzable bands and were included in the final quantification.RESULTS: In renal tissue, CTGF levels (mean±SD) were highest in Negative Control Group (0.81±0.06). Both the Metformin Group (0.58±0.14) and SGLT2i Group (0.57±0.33) demonstrated a trend toward reduced CTGF expression. In chorioretinal tissue, CTGF values were relatively similar across groups (Healthy Control: 0.67±0.05; Negative Control: 0.63±0.12), with Metformin Group (0.61±0.12) and SGLT2i Group (0.64±0.22) showing a modest reduction trend.CONCLUSION: In diabetic rats, CTGF expression levels are markedly increased. Following treatment with metformin and SGLT2i, CTGF expression demonstrates a noticeable reduction trend.KEYWORDS: SGLT2 inhibitor, metformin, connective tissue growth factor, cellular communication network factor 2, renal, retina